Faculty Wellness of a Higher Education Institution in the New Normal Time: Basis for the Personal and Professional Development Program - Geronimo, Cecilia A.; Inasoria, Romeo DC.; Geronimo, Audie L.; Geronimo, Deane Genevive G.; Esguerra, Renalyn C. (Future Science / FSH-PH Publications, 2023)
This study aimed to describe the status of faculty wellness in terms of the eight dimensions of wellness such as emotional, environmental, financial, intellectual, occupational, physical, social, and spiritual. Also, the challenges encountered by the faculty on the eight dimensions of wellness during the new normal time. The mixed methods of research were utilized, the constructed and validated questionnaire were responded by 277 faculty members of the HEI and ten randomly selected faculty members were interviewed. The results reveal that the physical wellness got the rating of occasionally while the other seven wellness got the rating of frequently, which implies that majority of the faculty were frequently practicing or doing the item descriptions of the eight dimensions of wellness. For the challenges encountered, the findings show that the spiritual challenge had a rating of seldom while the other ten challenges got the rating of sometimes, which means that the faculty encountered most of the challenges on the other seven dimensions of wellness, and the ranked first three were physical, occupational, and social. The results of the interview present the faculty’s good and not that good experiences with coping mechanisms during the new normal time. The researchers concluded that the status of the eight dimensions of faculty wellness should always be checked and monitored to maintain a smart, healthy, and responsive faculty. Eight personal and professional development programs were proposed to maintain and enhance the faculty wellness of the faculty in the HEI.